The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1559325817690849
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormal Brain Connectivity Spectrum Disorders Following Thimerosal Administration

Abstract: Background:Autism spectrum disorder (ASD), tic disorder (TD), and hyperkinetic syndrome of childhood (attention deficit disorder [ADD]/attention deficit hyperactivity disorder [ADHD]) are disorders recently defined as abnormal connectivity spectrum disorders (ACSDs) because they show a similar pattern of abnormal brain connectivity. This study examines whether these disorders are associated with exposure to thimerosal, a mercury (Hg)-based preservative.Methods:A hypothesis testing case-control study evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The term Autism Spectrum Disorders (ASD) encompasses a wide range of heterogeneous alterations of neural development characterized by three basic features: Impaired social interaction, language and communication abnormalities and stereotypical behavior. Although the etiology of ASD is debated and still largely unclear (Yenkoyan et al, 2017;Geier et al, 2017), the pathogenesis seems to be associated with alterations of the immune system and neuro-inflammation. Thus, we recently hypothesized that infections or inflammation at the level of the deep cervical nodes lead to impaired lymphatic drainage from the brain lymphatic system with consequent stagnation of lymph in the brain, disruption of neuronal connections, accumulation of metabolites and toxicants, neuroinflammation and alterations of the brain intrinsic microbiota (Bradstreet et al, 2015;Ruggiero, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The term Autism Spectrum Disorders (ASD) encompasses a wide range of heterogeneous alterations of neural development characterized by three basic features: Impaired social interaction, language and communication abnormalities and stereotypical behavior. Although the etiology of ASD is debated and still largely unclear (Yenkoyan et al, 2017;Geier et al, 2017), the pathogenesis seems to be associated with alterations of the immune system and neuro-inflammation. Thus, we recently hypothesized that infections or inflammation at the level of the deep cervical nodes lead to impaired lymphatic drainage from the brain lymphatic system with consequent stagnation of lymph in the brain, disruption of neuronal connections, accumulation of metabolites and toxicants, neuroinflammation and alterations of the brain intrinsic microbiota (Bradstreet et al, 2015;Ruggiero, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Memory recall requires reconstruction of elements scattered in disparate parts of the brain to be linked together by associations and neural networks [38, 39]; in other words, it requires global processing. Hg is known to destroy long-range connections in the brain, the connections that bring disparate parts of the brain together [40], and such phenomena was previously observed among infants receiving increased ethyl-Hg exposure [41]. On the other hand, the third test, the DSST, did not show effects from Hg exposure.…”
Section: Discussionmentioning
confidence: 95%
“…The link between thimerosal and other developmental disabilities (e.g., speech problems or learning difficulties) has also been evaluated and found to demonstrate no association between exposure to thimerosal in vaccines and these disabilities [ 13 ]. In contrast, longitudinal studies have found a correlation between higher thimerosal exposure from vaccines and ASD diagnosis [ 63 , 64 ].…”
Section: Mercury Poisoning and Its Link To Developmental Disabilities And Autismmentioning
confidence: 99%